PEREMPUAN DALAM MEDIA MASSA DI INDONESIA: ANALISIS ISI MEDIA MASSA TENTANG SOSOK PEREMPUAN DALAM PARADIGMA KRITIS - Islam, Nurul (Yinyang: Jurnal Studi Islam Gender dan Anak, 2008)
Capitalistic ideology covered with economic logic modifies media as fascinating profit resource with industry setting, namelywoman’s exploitation. This hegemony creating historical logic that reduced in to superstructure pattern of thought that have bias into socialorder. Individual collectivity in social life brings social responsibility value as conception that have to notice to preserve individual self image insocial sphere. Inasmuch language—verbal and non-verbal—is a communication that has positive and negative bias to other individual.